2018
DOI: 10.1891/0886-6708.vv-d-17-00072
|View full text |Cite
|
Sign up to set email alerts
|

Help-Seeking Among Abused Women With Pets: Evidence From a Canadian Sample

Abstract: A growing body of research has highlighted the significant co-occurrence of violence against women and companion animals in abusive households. Collectively, this work has also documented that sizable proportions of women with pets sampled report that they delayed leaving their partner due to fear for their pets’ safety. Using data from 86 residents of 16 battered women’s shelters in Canada, this study begins to tease apart the relationship between five types of animal maltreatment (emotional abuse, threats to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 45 publications
1
34
0
Order By: Relevance
“…Women who own pets or livestock face additional barriers to leaving. Research has shown that many survivors have especially strong bonds with their pets (Barrett et al 2018), and pets are an important source of comfort and emotional support. Being separated from companion animals adds to the trauma of leaving.…”
Section: Geographic Barriers By Distancementioning
confidence: 99%
“…Women who own pets or livestock face additional barriers to leaving. Research has shown that many survivors have especially strong bonds with their pets (Barrett et al 2018), and pets are an important source of comfort and emotional support. Being separated from companion animals adds to the trauma of leaving.…”
Section: Geographic Barriers By Distancementioning
confidence: 99%
“…While social safety nets are most often considered in relation to human social supports, there is mounting evidence that supportive relationships can be in the form of companion pets or service animals. Just as many women in an abusive situation may feel unable to leave due to concerns about her children, they may also be unwilling to leave behind a beloved pet that might not be welcome in transitional housing (Barrett et al, 2018;Stevenson et al, 2018). Owning a pet is associated with positive benefits, such as helping the individual maintain a positive self-image, increasing quality of life, reducing anxiety, or hyperarousal associated with PTSD, or even providing a basis for strengthening human social connections through social participation (Wood et al, 2015;Brooks et al, 2018;Wells, 2019).…”
Section: Relationships and The Social Safety Netmentioning
confidence: 99%
“…Domestic violence service providers are wise to take seriously reports of animal cruelty because domestic abusers who hurt animals also tend to use more extreme violence against humans (Barrett, Fitzgerald, Peirone, Stevenson, & Cheung, 2018), with abusers who emotionally harm animals being the most likely to do so to exert power and control over their human victims (Fitzgerald et al, 2019).…”
Section: Animal Abuse Often Means Increased Violence Against Humansmentioning
confidence: 99%
“…It is now well-established that one factor preventing many victims/survivors of domestic violence from seeking help is unwillingness to leave companion animals with perpetrators (Ascione et al, 2007;Barrett et al, 2018;Flynn, 2000;. For example, Barrett et al (2018) found that concern over companion animals often contributes to a woman's decision to return to her abuser after having initially severed the relationship.…”
Section: Victims/survivors Unwilling To Leave Without Petsmentioning
confidence: 99%